Fatigue reliability model for steel railway bridges. Issue 12 (1st December 2016) - Rakoczy, Anna M.; Nowak, Andrzej S.; Dick, Stephen
Abstract: Railway bridges are exposed to repetitive high stress due to the live load which may lead to failure even when the stress level is lower than the allowable stress. Therefore, components and connections need to be analysed for possible damage caused by fatigue. The basic approach for estimating the remaining fatigue life of a structure element is to use S – N curves. However, those laboratory specimens tested with a constant-amplitude stress range show a wide range variability in the results. This means that fatigue resistance has to be considered as a random variable. If load and resistance parameters are random variables, structural performance should be measured in terms of reliability. The objective of this study is to present a reliability model for the fatigue limit states demonstrated on a typical steel railway bridge. The results from the reliability analysis for the fatigue limit state are presented for various time periods from 10 to 100 years and three cases of operating conditions. In each considered case of load, the lowest reliability indices were obtained for the riveted angle in the stringer-to-floor-beam connection which means that this member has the highest probability of fatigue crack development in the entire bridge.